ANCA-associated vasculitis following Oxford-AstraZeneca COVID-19 vaccine in Brazil: Is there a causal relationship? A case report - Zamoner, Welder; Scardini, Julia Baldon; De Dio, Bruna Jordana; Marques, Amanda de Melo; Silva, Vanessa dos Santos; Garcia, Aline Lutz; dos Santos, Daniela Cristina; Viero, Rosa Marlene (Frontiers in Medicine, 2022)
This article presents a case of rapidly progressive glomerulonephritis following the Oxford-AstraZeneca COVID-19 vaccine in a female patient 58 years old. After 5 days, she presented fatigue, paleness, arthralgia on hands, knees, ankles, foamy urine, and elevated blood pressure. Exams showed serum creatinine of 2.2 mg/dL (baseline creatinine of 1.0 mg/dL). Urinalysis revealed hematuria, and her 24-h urinary protein excretion was 4.4 g. Additional exams showed hypercholesterolemia, severe anemia, and normal serum albumin. Testing of antineutrophil cytoplasmic antibodies anti-myeloperoxidase was positive at a titer of 1/80. Serum and urine protein electrophoresis and other exams showed no alterations. She was started on steroid pulse therapy after worsening kidney function, reaching serum creatinine of 3.3 mg/dL. A kidney biopsy revealed crescentic glomerulonephritis with glomerular sclerosis, fibrous crescents, interstitial fibrosis, and tubular atrophy. Induction therapy was given with intravenous cyclophosphamide 0.5 g/m2 for 6-monthly pulses, followed by maintenance therapy with oral azathioprine at 2 mg/kg and prednisone tapering. The patient did not develop any complications during the induction therapy, and is currently on maintenance therapy with a serum creatinine of 1.87 mg/dL.